Assembling tin dioxide nanorods on carbon nanotubes by a chemical solution method. Issue 168 (2nd January 2016) - Li, Rongkai; Chen, Dongping; Lai, Mengling; Li, Dongxu
ABSTRACT: Nanocomposites have significant potential in development of advanced materials and nanotechnology applications. Here, multi-walled carbon nanotubes (MWCNTs) sheathed with tin dioxide (SnO2 ) nanorods by a two-step chemical solution route are reported. Hydrolyzing of MWCNTs and SnCl4 ·5H2 O at a near room temperature followed by alkali-assisted hydrothermal process resulted in perfect SnO2 coating on MWCNTs. Based on the XRD and TEM results, we found the nanoscale SnO2 rods covered densely on MWCNTs.